Effectiveness of Counseling Group Behavioral Aversion Techniques and REBT Cognitive Dispute Techniques to Reduce Adolescent Smoking Behavior - Irin Febry Ikhtiarawati; Purwati Purwati; Astiwi Kurniati (Prosiding University Research Colloquium, 2022)
This study aims to examine the effectiveness of group counseling behavioral aversion techniques and cognitive dispute for smoking behavior. This research is an experimental study. The research used is Quasi Experiment. using the Nonequivalent Control Group Design method with one treatment. The study used 2 groups, namely experimental group 1 and experimental group 2 as a comparison. In determining the sample group, researchers used non-probability sampling with purposive sampling technique, namely the sample that had been determined. In this study, teenagers smoked. The results of the prerequisite test show that the data is normally distributed and has a homogeneous variance and the results of the analysis through the ANOVA test have a significance result of 0.000, which means less than 0.05, the conclusion is Ho is rejected and Ha is accepted. Based on the results of the analysis, the cognitive dispute group counseling and aversion technique have an effect on reducing smoking behavior.